OPTIMALISASI PELAKSANAAN KURIKULUM SISTEM MAYOR-MINOR PROGRAM PENDIDIKAN SARJANA INSTITUT PERTANIAN BOGOR - Sutoro Sutoro; Yonny Koesmaryono; Hari Wijayanto (School of Business, Bogor Agricultural University (SB-IPB), 2016)
This study aims to 1) evaluate the implementation of major-minor curriculum system in IPB Undergraduate Program, 2) identify factors leading to less optimized implementation of the major-minor curriculum system in IPB Undergraduate Program and 3) design strategies to optimize the implementation of the major-minor curriculum system in IPB Undergraduate Program. Analytical Hierarchy Process was utilized as the method of study. The results showed that the implementation of the major-minor curriculum system in IPB Undergraduate Program is still considered to be less optimal. Factors influencing the implementation of the major-minor curriculum system in IPB Undergraduate Program, according to its priority, include: 1) the availability of competent and committed teaching staffs, 2) the availability of adequate lecturing facilities and infrastructure, 3) the availability of lecture schedule to accommodate students who choose minor curriculum, and 4) the availability of reliable and IT-based Academic Information System (SIMAK). Strategies to optimize the implementation of major-minor curriculum system in IPB Undergraduate Program, according to its priority, include; 1) improving the competence and commitment of teaching and educational staffs, 2) increasing the commitment of departments and faculties to facilitate the fulfillment of minor curriculum schedules, 3) providing adequate facilities and infrastructure to implement the major and minor curriculum system, and 4) providing lecture schedules that can accommodate the needs of students who choose minor curriculum.Keywords: analytical hierarchy process, optimization, major-minor curriculum systemABSTRAKPenelitian ini bertujuan 1) mengevaluasi pelaksanaan kurikulum sistem mayor-minor pada Program Pendidikan Sarjana IPB, 2) mengidentifikasi faktor-faktor yang menyebabkan kurang optimalnya pelaksanaan kurikulum sistem mayor-minor pada Program Pendidikan Sarjana IPB dan 3) merancang strategi untuk mengoptimalkan pelaksanaan kurikulum sistem mayor-minor Program Pendidikan Sarjana IPB. Metode penelitian yang digunakan Analytical Hierarchy Prosess. Hasil penelitian menunjukkan bahwa pelaksanaan kurikulum sistem mayor-minor Program Pendidikan Sarjana IPB selama ini masih belum optimal. Faktor-faktor yang berpengaruh terhadap pelaksanaan kurikulum sistem mayor-minor pada Program Pendidikan Sarjana di IPB, berdasarkan urutan prioritas adalah;1) ketersediaan staf pengajar yang kompeten dan berkomitmen tinggi,2) ketersediaan sarana dan prasarana ruang perkuliahan yang memadai,3) tersedianya jadwal perkuliahan yang dapat mengakomodir keinginan mahasiswa yang memilih minor dan 4) ketersediaan Sistem Informasi Akademik (SIMAK) yang handal dan berbasis IT. Strategi optimalisasi pelaksanaan kurikulum sistem mayor-minor pada Program Pendidikan Sarjana IPB, berdasarkan urutan prioritas adalah; 1) meningkatkan kompetensi dan komitmen staf pendidik dan staf kependidikan,2) meningkatkan komitmen departemen dan fakultas untuk memfasilitasi agar dapat memenuhi jadwal minor,3) menyediakan sarana dan prasarana yang memadai untuk pelaksanaan kurikulum sistem mayor minor dan 4) menyediakan jadwal perkuliahan yang bisa mengakomodir keinginan mahasiswa yang memilih minor.Kata kunci: analytical hierarchy prosess, optimalisasi, kurikulum sistem mayor-minor